1989
DOI: 10.1126/science.2658062
|View full text |Cite
|
Sign up to set email alerts
|

The Neuronal Growth-Associated Protein GAP-43 Induces Filopodia in Non-Neuronal Cells

Abstract: The neuron-specific protein GAP-43 is associated with the membrane of the nerve growth cone and thus may be important to the activity of this distinctive neuronal structure. Transient transfection of COS and NIH 3T3 cells with appropriate vectors resulted in expression of GAP-43 in these non-neuronal cells; as in neurons, transfected GAP-43 associated with the membrane. In addition, many long fine filopodial processes extended from the periphery of such transfected cells. Stable CHO cell lines expressing GAP-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
2
2

Year Published

1994
1994
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(93 citation statements)
references
References 28 publications
5
84
2
2
Order By: Relevance
“…Rather, they were similar to the filopodia-like processes budding from B-50/GAP-43-overexpressing non-neuronal cells (Zuber et al, 1989;Yankner et al, 1990;Widmer and Caroni, 1993;Verhaagen et al, 1994). This observation indicates that B-50/GAP-43-induced Purkinje cell sprouts are unable to establish new synaptic connections.…”
Section: B-50/gap-43 Overexpression Does Not Modify the Intact Purkinmentioning
confidence: 82%
“…Rather, they were similar to the filopodia-like processes budding from B-50/GAP-43-overexpressing non-neuronal cells (Zuber et al, 1989;Yankner et al, 1990;Widmer and Caroni, 1993;Verhaagen et al, 1994). This observation indicates that B-50/GAP-43-induced Purkinje cell sprouts are unable to establish new synaptic connections.…”
Section: B-50/gap-43 Overexpression Does Not Modify the Intact Purkinmentioning
confidence: 82%
“…GAP-43 transfected into non-neuronal cells is known to induce filopodia (Zuber et al, 1989). We showed that the repetitive stimulation is favorable for filopodial sprouting.…”
Section: Dependence On Ca2+mentioning
confidence: 87%
“…Studies on the neuronal proteins GAP-43 and paralemmin show that palmitoylation is important for localizing these proteins to filopodia (Zuber et al, 1989a(Zuber et al, , 1989bKutzleb et al, 1998). In contrast, dual palmitoylation of PSD-95 is necessary for appropriate postsynaptic localization to dendritic spines (Craven et al, 1999;El-Husseini et al, 2000;El-Husseini and Bredt, 2002).…”
Section: Introductionmentioning
confidence: 99%